A influência da escola de tempo integral sobre a qualidade de vida infantil - Lima, Carlos Henrique de Freitas; Souza, Daniel Gottardo; Neiva, Cassiano Merussi [UNESP]; Tonello, Maria Georgina Marques; Cano, Maria Aparecida Tedeschi (My University, 2014)
This study aims to evaluate the quality of life of students aged 7 to 12 years in two municipal schools in the municipality of Minas Gerais. One offers full-time care to their students with extracurricular activities and other school offers only the normal. We used the questionnaire AUQEI, Autoquestionnaire Qualité de Vie Enfant Image. The questionnaire was administered to 232 children. Through this study, we observed that the proportion of children with a good Quality of Life was higher in school full time (81%), compared to the normal school hours (58%). Therefore, it is concluded that the school offers an extended workday, is set in an area rich able to develop the maximum potential of children and their personal skills, which will reflect positively on their quality of life.

O objetivo deste estudo foi avaliar a Qualidade de Vida de crianças com idade entre 7 e 12 anos de duas escolas públicas, do município de Minas Gerais. Uma delas oferece atendimento em período integral com atividades extracurriculares e a outra escola oferece período parcial de quatro horas diárias. Utilizou-se para a coleta de dados, o questionário AUQEI, Autoquestionnaire Qualité de Vie Enfant Imagé, aplicado em 232 crianças. Através deste estudo, foi possível verificar que a proporção de crianças que apresentaram uma boa qualidade de vida foi maior na escola de período integral (81%) se comparada à escola de horário parcial (58%). Concluiu-se que a escola que oferece uma jornada diária ampliada, se configura em um espaço riquíssimo capaz de desenvolver as potencialidades máximas das crianças e suas habilidades pessoais.
Keywords: Quality of life; Children; School; Health improvement; Qualidade de vida; Crianças; Escola; Promoção de saúde